Effect of Feeding Strategies on the Development of Fulminant Necrotizing Enterocolitis - Hartman, Heather A.; Pennell, Christopher; Aronoff, Stephen; Arthur, L. Grier (European Journal of Pediatric Surgery, 2020)
Introduction Necrotizing enterocolitis (NEC) causes significant neonatal morbidity. A subset of infants experience precipitous decline and death from fulminant-NEC (F-NEC). We sought to determine the effect of feeding practices on the development of this more virulent form of NEC.Materials and Methods Premature neonates developing Bell's stage II or III NEC between May 2011 and June 2017 were reviewed. Infants were stratified as having NEC or F-NEC, defined as NEC-totalis or NEC causing rapid decline and death within 72 hours. Risk factors extracted included demographics, gestational age, and weight at NEC diagnosis. Feeding data extracted included age at first feed, caloric density, type of feed (breast milk or formula), and whether full volume feeds were reached. Univariate analysis and multivariate analysis were performed.Results A total of 98 patients were identified, of which 80 were included. In total, 57 patients had NEC and 23 had F-NEC. Reaching full volume feeds was associated with F-NEC on both univariate and multivariate analysis (37.9 vs. 4.5%; odds ratio: 67, 95% confidence interval: 6.606–2041, p = 0.003). Infants developing F-NEC achieved full feeds earlier (22.5 vs. 19.8 days, p = 0.025) on univariate but not multivariate analysis. There was no difference in the rates of NEC and F-NEC among infants receiving breast milk (standard or fortified) or formula (standard or increased caloric density; p = 0.235).Conclusion Among premature neonates with NEC, reaching full volume feedings was associated with a nearly 70-fold increased risk of F-NEC. Assuming it was possible to predict an infant's development of NEC, alternative feeding regimens might reduce the risk of F-NEC in this population.
Keywords: necrotizing enterocolitis; fulminant necrotizing enterocolitis; necrotizing enterocolitis totalis; pediatric surgery